The ANALISIS STILISTIKA DAN SEMIOTIKA DALAM LAGU POP BALI YANG BERJUDUL ANGKIHAN BAAN NYILIH - Ni Komang Aryani Aryani; Ni Wayan Apriani; I Wayan Jatiyasa (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
This study has two objectives, namely to describe stylistics and semiotics in the lyrics of the song entitled "Angkihan Baan Nyilih". This research is a qualitative descriptive study. The literary approach used is a mythical approach and is combined with a mimetic approach. Data collection uses the document recording method. The data processing method is a descriptive method with the stages of data reduction, data presentation and conclusion drawing. The results showed that the stylistic elements contained in the lyrics of the song "Angkihan baan Nyilih" are phonemes/sounds, diction, syntactic forms, discourse and stanzas, language styles and imagery. The element of semiotics in the lyrics of the song "Angkihan baan Nyilih" is using the Semiotics theory of Ferdinand De Saussure, namely the existence of markers and signifieds.